Withdrawal of active treatments in terminally ill heart failure patients. (1st August 2021) - Sacco, A.; Morici, N.; Villanova, L.; Viola, G.; Lissoni, B.; Forni, L.; Mazza, U.; Oliva, F.
Abstract: Introduction: Heart failure (HF) constitutes a growing public health problem in aging societies: when pharmacological therapies fail, HF can be sustained intensively if patients are eligible for either orthotopic heart transplantation (OHT) or mechanical ventricular assistance, otherwise additional treatments could be inappropriate. In December 2017 Italian Legislator brought in the provisions regarding the end-of-life choices, including indications for withdrawing and withholding life-sustaining therapies. The aim of our study was to provide an overview of the daily practice of our center with regard to terminally ill HF patients. Methods and results: In April 2019 the 7 intensivist cardiologists and 21 nurses of a tertiary ICCU were asked in, to complete a questionnaire relating to a hypothetical terminally ill HF patient for whom the decision to withdraw active treatment had been made. To assess current practice, we also identified patients who died in the previous 12 months. Out of 29 deceased patients, 18 were identified as terminally ill HF, with no indications for therapy upgrading. We observed a striking disparity between belief and practice. Conclusions: Our survey showed that the care of terminally ill HF patients in our ICCU was characterized by aggressive use of medical therapy and invasive technology. The wide disparity between belief and practice could be in part a consequence of lack of professional training, with regard to law, ethics and communication techniques. Highlights: In Italy health professionals lack of adequate training in ethics and bioethics HF constitutes a growing public health problem in aging societies There are scant data about terminally ill HF patients in Intensive Cardiac Care Unit